Taxonomy and physiology of heterofermentative Lactobacillus species including isolates from South African red wines - Dicks, Leon Milner Theodore, 1961- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1985.